A method for preparing a high-starch-filled PBAT composite film

By using a twin screw extruder for pre-crosslinking and high-temperature dynamic crosslinking in PBAT composites, the compatibility and mechanical properties of PBAT and starch are improved, the problem of poor interface adhesion is solved, and high starch filling is achieved High mechanical properties and low cost production under quantity.

CN117603481BActive Publication Date: 2025-02-14ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202311761234.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2025-02-14
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

In the prior art, the interface adhesion between PBAT and starch is poor, resulting in limited starch filling amount and limiting the mechanical properties of PBAT composite materials.

Method used

The twin-screw extruder is used to perform pre-crosslinking treatment, and the starch, plasticizer, initiator, crosslinking agent and lubricant are premixed to prepare pre-crosslinked thermoplastic starch (TPS) particles, and then blend and extrude with PBAT. The compatibility and mechanical properties of starch and PBAT are improved by dynamic crosslinking at high temperatures.

Benefits of technology

With high starch filling, the mechanical properties of PBAT composite films have been significantly improved, reducing the cost of PBAT products. At the same time, the process flow is simple and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0004618623000000011
    Figure HDA0004618623000000011
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high starch content filled PBAT composite film, which comprises the following steps: (1) premixing starch, plasticizer, initiator, crosslinking agent and lubricant in a high-speed mixer according to a proportion, and then extruding and granulating with a twin-screw extruder to obtain pre-crosslinked TPS particles; (2) blending and extruding the pre-crosslinked TPS particles and PBAT in a twin-screw extruder to obtain a high starch content filled PBAT composite film. The composite film prepared by the present invention still has a high tensile strength under a high starch content, and can effectively reduce the cost of PBAT products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biodegradable plastic film preparation, and in particular to a method for preparing a PBAT composite film filled with a high amount of starch. Background Art

[0002] In recent years, biodegradable plastics have attracted widespread attention as a substitute for traditional non-degradable plastics. PBAT (polybutylene terephthalate-adipate) is a synthetic polymer based on fossil resources, 100% biodegradable, and widely used in the field of film packaging. However, compared with PE, the high cost of PBAT seriously limits its widespread application.

[0003] Starch has the advantages of abundant raw material sources, low cost, fast degradation, wide availability, and non-toxicity. Using it as a filler can effectively reduce the cost of PBAT products and make the filled PBAT have a faster degradation rate; however, the blending of hydrophobic PBAT and hydrophilic starch will make their interfacial adhesion poor, resulting in a significant decrease in their mechanical properties, limiting the amount of starch filling.

[0004] In order to improve the compatibility of starch and PBAT, starch can be pre-treated. For example, the patent "CN109111709A" discloses a PLA / PBAT biodegradable composite material containing corn starch and a preparation method thereof. Compared with ordinary starch, the starch after coupling treatment can enhance the compatibility with PLA / PBAT resin. For example, the patent "CN114106531A" discloses a starch / PBAT degradable composite material and a preparation method thereof. The tensile strength of the starch / PBAT degradable composite material is improved by using a strong interaction between a plasticizer (epoxidized soybean oil) and frankincense (the main component is frankincense acid) through intermolecular bonding. However, the tensile strength of starch itself is low, and simply improving the compatibility of starch with resin cannot effectively increase the starch filling amount. CN 116535831 A discloses a preparation method of PBAT filled and modified with thermoplastic cross-linked starch, wherein the preparation method obtains thermoplastic cross-linked starch by reacting starch with plasticizer and cross-linking agent B in sequence, thereby improving the compatibility between starch and PBAT; and then, while the thermoplastic cross-linked starch is filled and modified with PBAT, cross-linking modification of PBAT is performed to compensate for the loss of mechanical properties caused by starch filling, thereby obtaining a thermoplastic cross-linked starch filled and modified PBAT with good mechanical properties and low cost. In the preparation method, although the thermoplastic cross-linked starch can improve the compatibility between starch and PBAT compared with unmodified starch, the particle size of the thermoplastic cross-linked starch obtained after cross-linking is relatively large, and it is still difficult to disperse in PBAT, so the mechanical properties of PBAT will be lost due to starch filling. Therefore, in the preparation method, while the thermoplastic cross-linked starch is filled and modified with PBAT, a cross-linking agent A is also added to cross-link and modify PBAT to further improve the mechanical properties of PBAT. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies and provide a method for preparing a high starch content filled PBAT composite film.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a high starch content filled PBAT composite film comprises the following steps:

[0008] (1) Starch, plasticizer, initiator, crosslinking agent and lubricant are premixed in a high-speed mixer according to a certain proportion, and then extruded and granulated by a twin-screw extruder to obtain pre-crosslinked TPS particles. The twin-screw extruder is a parallel co-rotating twin-screw extruder, the aspect ratio of the screw is greater than 20:1 and less than 56:1, the temperature of the first to tenth sections of the extruder is 80-120°C, the die temperature is 100-120°C, and the rotation speed is controlled at 80-200rpm; the crosslinking agent is triallyl isocyanurate (TAIC); based on the total mass of starch, plasticizer, initiator, crosslinking agent and lubricant being 100%, the mass percentage of each component is: starch 70-80%, plasticizer 18-28%, peroxide initiator 0.2-0.6%, crosslinking agent 0.3-2.0%, and lubricant 0.1-0.5%;

[0009] (2) Pre-crosslinked TPS particles and PBAT are mixed and extruded into granules in a twin-screw extruder, wherein the twin-screw extruder is a parallel co-rotating twin-screw extruder, the screw aspect ratio is greater than 20:1 and not more than 56:1, the temperature of the first to tenth sections of the extruder is 150-190°C, the die temperature is 150-170°C, and the rotation speed is controlled at 80-200rpm; then, film blowing is performed to obtain a high starch content filled PBAT composite film; based on the mass of the pre-crosslinked TPS particles and PBAT as 100%, the mass percentages of the pre-crosslinked TPS particles and PBAT are 60-30% and 40-70%, respectively.

[0010] The crosslinking agent of the present invention is triallyl isocyanurate (TAIC), which has three double bond functional groups and can react with starch and PBAT under the action of peroxide to form crosslinks. Starch, plasticizer, initiator, crosslinker, and lubricant are first prepared into pre-crosslinked thermoplastic starch (TPS) particles by a high mixer and a twin-screw extruder. Since the initiator decomposes slowly at the extrusion temperature, it will not cause the crosslinking of starch. Then the pre-crosslinked TPS particles and PBAT are melt-blended in a twin-screw extruder. Since the extrusion temperature is high at this time, the initiator decomposes quickly, which promotes the reaction of the crosslinker with starch and PBAT to form crosslinks. The crosslinker crosslinks the starch when TPS is sheared and dispersed, thereby improving the strength of the starch itself; at the same time, at the TPS / PBAT interface, the crosslinker also causes TPS and PBAT to co-crosslink, thereby improving the compatibility of the two. After extrusion granulation, the film is blown, and the resulting high-starch-filled PBAT composite film still has good mechanical properties at a high starch filling amount.

[0011] In the present invention, the starch can be one or more of corn starch, tapioca starch, potato starch, sweet potato starch, wheat starch, pea starch, and lotus root starch.

[0012] In the present invention, the plasticizer may be one or more of glycerol, sorbitol, urea, and ethylene glycol.

[0013] In the present invention, the initiator is 1,4-di-tert-butylperoxyisopropylbenzene (BIBP).

[0014] In the present invention, the lubricant may be one or more of stearic acid, butyl stearate, stearic acid monoglyceride, and oleamide.

[0015] In the present invention, the PBAT is polybutylene adipate terephthalate, and has a melt flow rate of 2-10 g / 10 min (190° C., 2.16 kg) and a terminal carboxyl content of 1-30 mol / ton.

[0016] In step (1) of the present invention, the specific conditions for premixing in a high-speed mixer are: the high-speed mixer temperature is 60-80° C., the rotation speed is 200-500 rpm, and the mixing time is 10-30 min.

[0017] In step (2) of the present invention, the film blowing conditions are: the temperature of the first to fourth extrusion stages is 140-170° C., the blowing ratio (die diameter: film bubble diameter) is 1:3, and the film blowing stretch ratio is 1.2.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The crosslinking agent used can react with both TPS and PBAT. While crosslinking TPS to improve its tensile strength, it can also improve the compatibility of TPS and PBAT.

[0020] (2) The composite film still has high tensile strength at high starch filling content, which can effectively reduce the cost of PBAT products.

[0021] (3) The composite film was prepared by a two-step method, firstly preparing pre-crosslinked starch particles at low temperature, and then achieving dynamic crosslinking by shearing at high temperature. Compared with the film directly blended with crosslinked starch and PBAT, it has better performance.

[0022] (4) High mixing, granulation, and film blowing, the process is simple, easy to operate, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the scanning electron microscope picture of the cross section of the film of control example 2 and embodiment 3. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0025] Example 1

[0026] Calculated by mass percentage, the pre-crosslinked thermoplastic starch (TPS) particles include 70% starch (corn starch), 29% plasticizer (glycerol), 0.2% peroxide initiator (1,4-di-tert-butylperoxyisopropylbenzene, half-life of 1 min at 182°C), 0.5% crosslinking agent (triallyl isocyanurate), and 0.3% lubricant (monoglycerol stearate).

[0027] Calculated by mass percentage, the composite film includes 70% PBAT and 30% pre-crosslinked TPS particles.

[0028] Preparation of pre-crosslinked TPS particles: starch, plasticizer, initiator, crosslinker, lubricant (all general commercial products) were weighed according to the formula, and all the raw materials were directly put into a 5L high-speed mixer (LN-G5L, Guangdong Lina Industrial Co., Ltd.), and blended at 60°C and 300rpm for 10min; then the mixture was added to a parallel co-rotating twin-screw extruder (φ20, L / D=36, Nanjing Juli Chemical Machinery Co., Ltd.) for mixing, plasticization, and extrusion, and the desired pellets were obtained after strand air cooling and pelletizing; the temperatures of each section of the extruder were: the temperatures of sections one to ten were 80, 85, 90, 100, 110, 120, 110, 100, 95, and 90°C, respectively, and the die temperature was 100°C; the rotation speed was 120rpm.

[0029] Preparation of micro-crosslinked TPS / PBAT composite film: PABT and pre-crosslinked TPS particles were weighed according to the formula and added to a parallel co-rotating twin-screw extruder (φ20, L / D=36, Nanjing Juli Chemical Machinery Co., Ltd.) for mixing, plasticization, and extrusion. The required pellets were obtained by stranding and air-cooling pelletizing; the temperature of each section of the extruder was: the temperature of the first to tenth sections was 150, 155, 160, 160, 170, 180, 170, 160, 155, 150°C, the die head temperature was 150°C; the speed was 120rpm. The obtained pellets were directly blown by a film blowing machine (XH-430B, Xihua Testing Instrument Co., Ltd.) to obtain a PBAT starch composite film. The temperature of the first to fourth sections of the film blowing extruder was 150, 160, 170, 150°C, the blowing ratio (die diameter: film bubble diameter) was 1:3, and the film blowing stretch ratio was 1.2.

[0030] The obtained film was subjected to a tensile property test according to GB / T1040.3-2006 to obtain data such as tensile strength and elongation at break.

[0031] Example 2

[0032] The other steps were the same as in Example 1, except that the amount of the crosslinking agent was increased from 0.5% to 1.0%.

[0033] Example 3

[0034] The other steps were the same as in Example 1, except that the amount of the crosslinking agent was increased from 0.5% to 2.0%.

[0035] Example 4

[0036] The other steps are the same as those in Example 3, but the amount of pre-crosslinked TPS particles in the composite film is increased to 40%.

[0037] Example 5

[0038] The other steps are the same as those in Example 3, but the amount of pre-crosslinked TPS particles in the composite film is increased to 50%.

[0039] Example 6

[0040] The rest is the same as Example 3, but the parallel co-rotating twin-screw extruder (φ20, L / D=36, Nanjing Juli Chemical Machinery Co., Ltd.) is changed to a production-type parallel co-rotating twin-screw extruder (φ35, L / D=52, Nanjing Juli Chemical Machinery Co., Ltd.), and the puncture resistance of the film is tested according to GB / T 37841-2019, and the heat sealing strength of the film is tested according to QB / T 2358-1998.

[0041] Example 7

[0042] The rest is the same as Example 4, but the parallel co-rotating twin-screw extruder (φ20, L / D=36, Nanjing Juli Chemical Machinery Co., Ltd.) is changed to a production-type parallel co-rotating twin-screw extruder (φ35, L / D=52, Nanjing Juli Chemical Machinery Co., Ltd.), and the puncture resistance of the film is tested according to GB / T 37841-2019, and the heat sealing strength of the film is tested according to QB / T 2358-1998.

[0043] Comparative Example 1

[0044] The other steps are the same as those in Example 1, but without adding initiator and crosslinking agent.

[0045] Comparative Example 2

[0046] Calculated by mass percentage, the cross-linked thermoplastic starch (TPS) particles include 70% starch (corn starch), 29% plasticizer (glycerol), 0.2% peroxide initiator (1,4-di-tert-butylperoxyisopropylbenzene), 2.0% cross-linking agent (triallyl isocyanurate), and 0.3% lubricant (monoglycerol stearate).

[0047] Calculated by mass percentage, the composite film includes 70% PBAT and 30% cross-linked TPS particles.

[0048] Preparation of cross-linked TPS particles: starch, plasticizer, initiator, cross-linking agent, lubricant (all of which are general commercial products) are weighed according to the formula, and all raw materials are directly put into a 5L high-speed mixer (LN-G5L, Guangdong Lina Industrial Co., Ltd.), and blended at 60°C and 300rpm for 10min; then the mixture is added to a parallel co-rotating twin-screw extruder (φ20, L / D=36, Nanjing Juli Chemical Machinery Co., Ltd.) for mixing, plasticization, and extrusion, and the desired pellets are obtained after strand air cooling and pelletizing; the temperature of each section of the extruder is: the temperature of sections one to ten is 150, 155, 160, 160, 170, 180, 170, 160, 155, 150°C, respectively, and the die head temperature is 100°C; the rotation speed is 120rpm.

[0049] Preparation of cross-linked TPS / PBAT composite film: PABT and cross-linked TPS particles were weighed according to the formula and added to a parallel co-rotating twin-screw extruder (φ20, L / D=36, Nanjing Juli Chemical Machinery Co., Ltd.) for mixing, plasticization, and extrusion. The required pellets were obtained by stranding, air cooling, and pelletizing; the temperature of each section of the extruder was: the temperature of the first to tenth sections was 150, 155, 160, 160, 170, 180, 170, 160, 155, 150°C, the die head temperature was 150°C; the speed was 120rpm. The obtained pellets were directly blown by a film blowing machine (XH-430B, Xihua Testing Instrument Co., Ltd.) to obtain a PBAT starch composite film. The temperature of the first to fourth sections of the film blowing extruder was 150, 160, 170, 150°C, the blowing ratio (die diameter: film bubble diameter) was 1:3, and the film blowing stretch ratio was 1.2.

[0050] Figure 1 The cross-sectional scanning electron micrographs of the PBAT starch films prepared in Control Example 2 (left) and Example 3 (right) are given. It can be seen from the figure that there are obvious particles in the composite film prepared in Control Example 2, while the pre-cross-linked TPS particles in the composite film prepared in Example 3 are smaller and better dispersed, and no obvious particles can be seen.

[0051] The obtained film was subjected to a tensile property test according to GB / T1040.3-2006 to obtain data such as tensile strength and elongation at break. The results are shown in Table 1.

[0052] Table 1

[0053]

Claims

1. A method for preparing a high starch content filled PBAT composite film, characterized in that: The preparation method comprises the following steps: (1) Starch, plasticizer, initiator, crosslinking agent and lubricant are premixed in a high-speed mixer according to a certain proportion, and then extruded and granulated by a twin-screw extruder to obtain pre-crosslinked TPS particles. The twin-screw extruder is a parallel co-rotating twin-screw extruder, the aspect ratio of the screw is greater than 20:1 and less than 56:1, the temperature of the first to tenth sections of the extruder is 80-120°C, the die temperature is 100-120°C, and the rotation speed is controlled at 80-200rpm; the crosslinking agent is triallyl isocyanurate; based on the total mass of starch, plasticizer, initiator, crosslinking agent and lubricant being 100%, the mass percentage of each component is: starch 70-80%, plasticizer 18-28%, peroxide initiator 0.2-0.6%, crosslinking agent 0.3-2.0%, and lubricant 0.1-0.5%; (2) Pre-crosslinked TPS particles and PBAT are mixed and extruded into granules in a twin-screw extruder, wherein the twin-screw extruder is a parallel co-rotating twin-screw extruder, the screw aspect ratio is greater than 20:1 and not more than 56:1, the temperature of the first to tenth sections of the extruder is 150-190°C, the die temperature is 150-170°C, and the rotation speed is controlled at 80-200rpm; then, film blowing is performed to obtain a high starch content filled PBAT composite film; based on the mass of the pre-crosslinked TPS particles and PBAT as 100%, the mass percentages of the pre-crosslinked TPS particles and PBAT are 60-30% and 40-70%, respectively.

2. The preparation method according to claim 1, characterized in that: The starch is one or more of corn starch, tapioca starch, potato starch, sweet potato starch, wheat starch, pea starch, and lotus root starch.

3. The preparation method according to claim 1, characterized in that: The plasticizer is one or more of glycerol, sorbitol, urea and ethylene glycol.

4. The preparation method according to claim 1, characterized in that: The initiator is 1,4-di-tert-butylperoxyisopropylbenzene.

5. The preparation method according to claim 1, characterized in that: The lubricant is one or more of stearic acid, butyl stearate, stearic acid monoglyceride, and oleamide.

6. The preparation method according to claim 1, characterized in that: The PBAT is polybutylene adipate terephthalate, and has a melt flow rate of 2-10 g / 10 min (190° C., 2.16 kg) and a terminal carboxyl content of 1-30 mol / ton.

7. The preparation method according to claim 1, characterized in that: In step (1), the specific conditions for premixing in a high-speed mixer are: the temperature of the high-speed mixer is 60-80° C., the rotation speed is 200-500 rpm, and the mixing time is 10-30 min.

8. The preparation method according to claim 1, characterized in that: In step (2), the film blowing conditions are as follows: the temperature of the first to fourth extrusion stages is 140-170° C., the blowing ratio is 1:3, and the film blowing stretch ratio is 1.2.

Citation Information

Patent Citations

  • A PLA / PBAT biodegradable composite material containing corn starch and a preparing method thereof

    CN109111709A

  • Starch-PBAT degradable composite material and preparation method thereof

    CN114106531A

  • Thermoplastic crosslinked starch filled and modified PBAT and preparation method thereof

    CN116535831A

  • Thermoplastic and PBAT blend and preparation method thereof

    CN103205021A

  • Starch / cellulose / PBAT composite film and preparation method thereof

    CN113248798A

Cited By

  • Preparation method of polyethylene glycol adipate-ethylene glycol terephthalate / thermoplastic starch composite film

    CN121378812A